Characterization of plant growth promoting potential of 3D-printed plant microbial fuel cells - Diane Pamela Entienza Palmero; Kristopher Ray Simbulan Pamintuan (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
Plant-Microbial Fuel Cell (PMFC) is an emerging technology that converts plant waste into electrical energy through rhizodeposition, offering a renewable and sustainable source of energy. Deviating from the traditional PMFC configurations, additive manufacturing was utilized to create intricate and efficient designs using polymer-carbon composites. Concerning the agricultural sector, the effect of 3D-printed PMFCs on the growth and biomass distribution of Phaseolus lunatus and Ipomoea aquatica was determined. The experiment showed that electrostimulation promoted the average daily leaf number and plant height of both polarized plants, which were statistically proven to be greater than the control (α = 0.05), by energizing the flow of ions in the soil, boosting nutrient uptake and metabolism. It also stimulated the growth of roots, increasing the root dry mass of polarized plants by 155.44% and 66.30% for I. aquatica and P. Lunatus against their non-polarized counterpart. Due to the biofilm formation on the anode surface, the number of root nodules of the polarized P. lunatus was 51.30% higher than the control, while the protein content in the PMFC setup was 42.22% and 8.26% higher than the control for I. aquatica and P. lunatus, respectively. The voltage readings resemble the plants' average growth rate, and the polarization studies showed that the optimum external resistances in the I. aquatica- and P. lunatus-powered PMFC were 4.7 kΩ and 10 kΩ, respectively. Due to other prevailing pathways of organic carbon consumption, such as methanogenesis, the effect of polarization on the organic carbon content in soil is currently inconclusive and requires further study.